Innovation in Building Digital Literacy: Stakeholder Challenges in Growing Suburban Communities - Taufiq Harris; A. Faizin; Ahmad Thohirin; Ali Romdhoni (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This study examines (a) the role of stakeholders in realizing innovation in building digital literacy programs in Gresik Regency, (b) stakeholder efforts in fostering digital literacy awareness, and (c) stakeholder challenges to realizing innovation in building digital literacy programs for suburban communities. Method: The research uses a qualitative approach with grounded theoretical research. The research was conducted in five villages in Gresik Regency, and the research subjects amounted to 40 informants. Data collection uses in-depth interviews, participant observations, and document studies. The analysis of lepangan data uses two methods: (a) an interactive data analysis model and (b) an analysis of the coding process and conclusion. Results: 1) The role of stakeholders in realizing innovation in building digital literacy programs in Gresik Regency starts from village elements and community leaders to become initiators and active participants to villagers in carrying out digital literacy program implementation activities; 2) Stakeholder participation is quite diverse, which is influenced by care, funds, and responsible persons, while the implementation of E-commerce platforms in the local community is very effective and the competition is open; 3) Facing several challenges, especially in terms of digital literacy, limited facilities and concern of the local community. Novelty: This research combines strategies to generate innovations in various aspects of digital literacy awareness. The critical role of an effective leader is to promote and implement digital education, as well as stakeholders to strengthen literacy education in the current digital era.